2010
DOI: 10.1186/1472-6963-10-177
|View full text |Cite
|
Sign up to set email alerts
|

Responsibility loadings for dental services by general dentists

Abstract: BackgroundResponsibility loadings determine relative value units of dental services that translate services into a common scale of work effort. The aims of this paper were to elicit responsibility loadings for a subset of dental services and to relate responsibility loadings to ratings of importance of the components of responsibility.MethodsResponsibility loadings and ratings of components of responsibility were collected using mailed questionnaires from a random sample of Australian private general practice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Accordingly, responsibility load is shaped by the employee's title and work content. Tasks that require more knowledge, decisionmaking, and skill carry a higher responsibility load (Brennan & Spencer, 2010). New administrative candidates have very little decision-making responsibility, which benefits relatively fewer people while they learn tasks that require limited skill and job components (Fried, Grant, Levi, Hadani, & Slowik, 2007).…”
Section: Relationship Between Workload and Responsibility Loadmentioning
confidence: 99%
“…Accordingly, responsibility load is shaped by the employee's title and work content. Tasks that require more knowledge, decisionmaking, and skill carry a higher responsibility load (Brennan & Spencer, 2010). New administrative candidates have very little decision-making responsibility, which benefits relatively fewer people while they learn tasks that require limited skill and job components (Fried, Grant, Levi, Hadani, & Slowik, 2007).…”
Section: Relationship Between Workload and Responsibility Loadmentioning
confidence: 99%
“…Some of these are based on time and time‐cost units . However, being restricted to time as the measure of relative value of services does not account for the responsibility aspects of service provision . Another approach is the use of fees to estimates RVUs, but fees may reflect other factors such as consumer perceptions, or infrastructure costs not directly related to the resources required to provide the service.…”
Section: Discussionmentioning
confidence: 99%
“…20 However, being restricted to time as the measure of relative value of services does not account for the responsibility aspects of service provision. 13 Another approach is the use of fees to estimates RVUs, 8 but fees T A B L E 3 Adjusted coefficients (SE) from ordered logit models of responsibility weight for dental services The observed variation in weights across service areas showed that dentists discriminated between services in a systematic and cognizant manner. Further, the logical variation observed provides an indication of face validity in that the discrimination in responsibility weights was consistent with clinical expectations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations